Keterampilan Teknik Dasar Dalam Permainan Bola Voli Pada Peserta Didik SMA Negeri 3 Tondano - Fabio Keane Manengkey (STIKES Columbia Asia Medan, 2025)
This study aims to evaluate the basic volleyball skills of 11th-grade students at SMA Negeri 3 Tondano. As part of physical education, volleyball plays a critical role in shaping students' physical abilities, character, and teamwork. Fundamental techniques such as overhand and underhand passing are essential foundations for success in the sport. This research employed a descriptive quantitative method with survey and test techniques, targeting 60 students. The instruments used were the Brady Wall Volley Test for overhand passing and the Brumbach Forearms Pass Wall Volley Test for underhand passing. The results revealed that the majority of students (100%) fell into the “very poor” category for both techniques. These findings highlight the need for more structured and intensive basic technique training, supported by appropriate teaching media and adequate sports facilities.